The ocular surface side effects of an anti-psychotic drug, clozapine. (2nd January 2016) - Ceylan, Erdinç; Ozer, Muhammet Derda; Yilmaz, Yusuf Cem; Kartal, Baki; Yildiz Ekinci, Dilbade; Çinici, Emine; Aksu Ceylan, Nihan
Abstract: Purpose : The purpose of this study is to investigate the effects of long-term clozapine usage on tear film stability and corneal topographic parameters. Material and methods : The study was conducted between March 2014 and November 2014. Thirty patients who were diagnosed of schizophrenia and have been under clozapine treatment for 2.73 ± 0.73 years (range 2–4 years) were involved in this study (group 1). Thirty healthy subjects (group 2) who have statistically similar demographic features compared with the group 1, were involved as a control group. Full ophthalmologic examination with biomicroscopy and indirect ophthalmoscopy was applied. Corneal topographic parameters were measured using the Pentacam HR and Schirmer test was done. Statistical analysis of the subjects was evaluated by using SPSS (for Windows version 16.0; SPSS Inc., Chicago, IL) program. Results : K 1 value was measured as 43.39 ± 0.17 D (43–43.50 D) and K 2 value was measured as 43.39 ± 0.06 D (43.30–43.50 D) in groups 1 and 2, respectively. In groups 1 and 2, K 2 values were noted as 43.86 ± 0.27 D (43.50–44.50 D) and 43.72 ± 0.18 D (43.50–44.00 D), respectively. Central corneal thickness was found to be 523.93 ± 15.66 µm (495–554 µm) and 550.13 ± 1.03 µm (520–580 µm) in groups 1 and 2, respectively. Corneal apex thickness was 525.86 ± 15.75 µm (497–556 µm) in group 1 and 551.60 ± 14.99 µm (521–581 µm) in group 2. The corneal thickness of thinnest location was 520.93 ± 15.60 µm (492–551 µm) and 548.06 ± 15.17 µm (518–578 µm) in groups 1 and 2, respectively. Corneal volume was determined as 58.13 ± 3.46 mm 3 (52–64 mm 3 ) in group 1 and 60.73 ± 3.76 mm 3 (54–66 mm 3 ) in group 2. The Schirmer test showed thichkness of 3.33 ± 0.72 mm (2–4 mm) and 13.60 ± 1.59 mm (11–16 mm) in groups 1 and 2, respectively. The mean fluorescein break-up time was 5.40 ± 1.50 s (3–8 s) and 12.46 ± 1.40 s (10–14 s) in groups 1 and 2, respectively. There was a statistically significant difference in the Schirmer test, fluorescein break-up time, central corneal thickness, corneal apex, and the thinnest corneal location thickness between the two groups. Conclusion : Clozapine may induce dry eye syndrome and thus may lead to morphological alterations in corneal parameters through its anticholinergic and antidopaminergic activities. Because of these corneal alterations, one should be aware of evaluating patients having diseases like glaucoma or preoperative selection of corneal refractive surgery candidates.